2006
DOI: 10.1249/01.mss.0000233803.48691.8b
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training and Reduction of Treatment Side Effects in Prostate Cancer Patients

Abstract: Progressive resistance exercise has beneficial effects on muscle strength, functional performance and balance in older men receiving androgen deprivation for prostate cancer and should be considered to preserve body composition and reduce treatment side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
301
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 269 publications
(318 citation statements)
references
References 27 publications
14
301
2
1
Order By: Relevance
“…All seven group-based exercise studies 4,58,59,61,62,65,66 tended to show significant improvements in at least two of the three domains of physical fitness assessed, namely muscular strength, muscular endurance and aerobic endurance. In contrast, only two of the four home-based studies that assessed physical fitness measures found any significant improvements, and these were only observed for aerobic endurance 51,64 .…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…All seven group-based exercise studies 4,58,59,61,62,65,66 tended to show significant improvements in at least two of the three domains of physical fitness assessed, namely muscular strength, muscular endurance and aerobic endurance. In contrast, only two of the four home-based studies that assessed physical fitness measures found any significant improvements, and these were only observed for aerobic endurance 51,64 .…”
Section: Resultsmentioning
confidence: 96%
“…All exceptions to this rule were observed for group-rather than home-based exercise and included significant increases in muscle mass 61 and quadriceps thickness 65,66 and a significant decrease in body fat percentage 4 . There was little effect of exercise mode on these responses as these changes were observed as a result of resistance 4,65 , aerobic 66 and combined resistance and aerobic exercise 61 .…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations